EVALUATION OF PHYSICOCHEMICAL PARAMETERS OF GROUNDWATER OF THE VILLAGES OF OSMANABAD DT., MAHARASHTRA, INDIA - HUSAIN A, SAYYED; PATEL B, SHANKAT; AURADE C, RAM (Innovare Journal of Sciences, 2020)
The analysis deals with the investigation of physicochemical parameter of ground water of the different villages of dist. Osmanabad (MS). The physicochemical parameter like, temperature, pH, electrical conductivity, total dissolved solids, turbidity, total hardness, calcium, magnesium, sodium, potassium, chloride, fluoride, Nitrate, Sulphate was determined. The results were compared with standards given by WHO and IS 10500. In the investigation, it is found that the ground water of some villages like kangara, irla gets slightly polluted.